Surveys of economic theory : growth and development, vol. II - Royal Economic Society (Great Britain); American Economic Society (London : Macmillan ; New York : St Martin's Press, 1965)
This volume covers: The Theory of Economic Growth: A Survey; Comparative Advantage and Development Policy; The Pure Theory of International Trade: A Survey; Regional Economics: A Survey.
"First published in the American economic review and the Economic journal."
Prepared for The American Economic Association and The Royal Economic Society.
Includes bibliographical references: p. 267-271.
rpm 04/10/2017
Loans
Keywords: Economics